THE URGENCY OF FORMING SPECIAL CRIMINAL LAWS FOR CRIMINALS COMMITTED BY CHILDREN IN CASES OF SEXUAL VIOLENCE AGAINST CHILDREN REVIEWED FROM THEORY OF LEGAL CERTAINTY - Imera Azzahra Alivia; Prija Djatmika; Nurini Aprilianda (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Sexual violence against children committed by child perpetrators is a serious issue in the criminal justice system in Indonesia. Currently, Indonesian criminal law does not specifically regulate a comprehensive handling mechanism for this case, thus causing problems in the application of fair law and providing optimal protection for children as victims and perpetrators. This study aims to analyze the urgency of establishing a special criminal law that handles criminal acts of sexual violence by children against other children. A normative legal approach with a conceptual approach, a legislative approach and a comparative approach and the theory of legal certainty are used in this study to explore the need for clearer and more responsive regulations. The results of the study indicate that the establishment of a special criminal law can provide better legal certainty, including appropriate protection and rehabilitation mechanisms for children as perpetrators and victims. This is important to ensure that the criminal justice system not only prioritizes punishment, but also protection and rehabilitation in accordance with the principle of the best interests of the child. The establishment of this special regulation can also strengthen the justice system to be more adaptive and responsive to the special characteristics of cases of child sexual violence.